(3GdRghQ GdeTQbI hGdfaMGJ GdYHbIs - (3jhSa Hf CMeO Hf eMeO Hf YKeGfs
(3ChdgG (B:s
(3jHOC HcJGH GdEjeGf Hbhdg (B: (3ddjejf eYfjGf dZI hEUWdGMkG aCeG ai GddZI agi s
(3BNQgG (B:s
(3hai gPjf GdcJGHjf eSGFd ef MhGTi GdEaGOI , hef hba Ydi Ndd CUdMI HYO ESJjaGA GdfXQ fLR fSGNI s
(3cJHJ GdYfGhjjf HGdMeQIs
(3bQf GdfSN (B:s
(3GdbQf GdJGSYs
(3JHUQI GdYfhGf (B:s
(3TQMs
(3GdJhKjbGJ GdeQLYjI (B:s
Keywords: (3Gdabg GdESdGejs